PENGARUH GAYA KEPEMIMPINAN DAN INTEGRITAS TERHADAP KINERJA ORGANISASI DENGAN KOMUNIKASI INTERNAL SEBAGAI VARIABEL MEDIASI DI STM MARSADA - Immanuel Fernando Hosea Manurung; Robert Tua Siregar; Elly Romy (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to analyze the influence of leadership style, integrity, and internal communication on organizational performance at STMi Marsada. The method used in this study is quantitative, with data processing using SPSS software version 26. The results of the path analysis show that leadership style (X1) has a significant influence on internal communication (Y), with a coefficient of determination of 19.0%. However, integrity (X2) does not show a significant influence on internal communication. In addition, the influence of leadership style (X1), integrity (X2), and internal communication (Y) on organizational performance (Z) shows that only the integrity variable has a significant influence on organizational performance, with a p-value of 0.028. The results of the Sobeli test confirm that the influence of leadership style on internal communication through organizational performance is significant, while the influence of integrity is not significant. Overall, this study reveals that leadership style and internal communication have an important role in improving organizational performance, although the contribution of integrity is relatively limited.